Dasar Pengembangan Kurikulum Menjadi Pengalaman Belajar - Famahato Lase (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2015)
The curriculum was developed based on a clear objective, which is to steer students to become desired people. There are things that must be considered in designing the curriculum, namely what is the objectives of the lesson to be achieved, what material can be used to achive the goal, how the material should be arranged to achive the goal, and how it can be evaluated to see the success of the goal. So, the students can aquire knowledge, skills, and functional values in the future. This is the meaning of curriculum development as learning experince